Sign and Guidance from the Perspective of the Qur’an “Divine Cosmic Signs, a Semantic Study” - Al- Yabroudi, Yusra Ahamd Tawfiq (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: This research aims at revealing the semantic relationships between divine cosmic signs and human guidance on the oneness of God (Allah) - Almighty-, through identifying the meaning of both sign and guidance, then revealing the most important divine cosmic signs mentioned in the holy Quran, such as stars, planets, moon, and sun. The study also observed the main connotations resulting from these signs through functions assigned to them by God and reveal their relationship with human guidance to the oneness of God. Methods: The inductive approach through extrapolating places where the divine cosmic signs were mentioned in the Qur’an, and then used the analytical approach represented in recognizing interpreters’ analyses and interpretations of verses referring to these signs. Results: The most significant finding of the study is that all divine signs created by God have specific functions and not created randomly, as they are related to the mind and heat guidance to the oneness of God. Conclusions: The need to prepare in-depth studies on the global phenomena and their relationship with the oneness of God, such as scientific miracles studies, and presenting them through dialogue forums or via radio and TV programs